Pertumbuhan, Produksi Biomassa, dan Kandungan Glikosida Steviol pada Lima Klon Stevia Introduksi di Bogor, Indonesia - Sinta, Masna Maya; Sumaryono, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Stevia rebaudiana Bertoni, a sweetener plant, has been cultivated in Indonesia since the early 1980s, but the yield is lower than in other countries. Five selected introduced stevia clones were planted at Megamendung, Bogor, Indonesia (6°39’ S, 106°56’ E, 800 m above sea level) on December 2014 until November 2015 to evaluate their growth and biomass yield. The growth and yield were observed from 6 to 12 months after planting. In addition, stevioside, rebaudioside A (reb A), and total steviol glycoside (TSG) contents of leaves were measured using high performance liquid chromatography (HPLC). At six months after planting, stem diameter was 8-11 mm, plant canopy diameter was 23-30 cm, plant height was 24-35 cm, and plant mortality was less than 5% except for clone BU at 30.7% due to Sclerotium attack. The plants flowered at different times, therefore had different harvest durations, from 4 weeks (clone BM) to 8 weeks (clone BP). The highest leaf yield was clone BM (6.04 ton ha-1 per year), followed by BX (4.91 ton ha-1 per year), and BP (4.38 ton ha-1 per year). From the five clones tested, clone BM was the best for leaf, TSG, and stevioside yields; whereas clone BS and BP were the best for reb A yield. Keywords: rebaudioside A, Stevia rebaudiana, stevioside, total steviol glycoside